2020
DOI: 10.3390/cancers12061664
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Histone Deacetylases and Inhibitors in Anticancer Therapy

Abstract: Histones are the main structural proteins of eukaryotic chromatin. Histone acetylation/ deacetylation are the epigenetic mechanisms of the regulation of gene expression and are catalyzed by histone acetyltransferases (HAT) and histone deacetylases (HDAC). These epigenetic alterations of DNA structure influence the action of transcription factors which can induce or repress gene transcription. The HATs catalyze acetylation and the events related to gene transcription and are also responsible for transporting ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 285 publications
(312 reference statements)
0
59
0
Order By: Relevance
“…The accumulation of cells in the S-phase as was found in our cells was in line with earlier observations that PLX induces accumulation of DLBCL cells in the S-phase ( Tonner et al, 2006 ). In earlier studies on HDAC combinations ( Eckschlager et al, 2017 ; Verza et al, 2020 ), it was shown that a modulating concentration of the HDAC inhibitor is able to enhance the efficacy of DNA targeted drugs, such as the cross-linker cisplatin, possibly by down regulation of DNA repair enzymes by the HDAC inhibitor. This is in line with the interaction data described in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accumulation of cells in the S-phase as was found in our cells was in line with earlier observations that PLX induces accumulation of DLBCL cells in the S-phase ( Tonner et al, 2006 ). In earlier studies on HDAC combinations ( Eckschlager et al, 2017 ; Verza et al, 2020 ), it was shown that a modulating concentration of the HDAC inhibitor is able to enhance the efficacy of DNA targeted drugs, such as the cross-linker cisplatin, possibly by down regulation of DNA repair enzymes by the HDAC inhibitor. This is in line with the interaction data described in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Belinostat (BLS) is a hydroxamic acid-based pan-histone deacetylase (HDAC) inhibitor that inhibits all of the zinc-dependent HDAC enzymes, with high affinity for the Class I, II and IV isozymes ( Eckschlager et al, 2017 ). HDAC inhibition results in an alteration in the degree of histone and non-histone protein acetylation, which in turn affects transcription of genes essential in cellular proliferation, cell cycle and DNA repair ( Verza et al, 2020 ). Hence BLS is an epigenetic drug ( Yeon et al, 2020 ) and is approved for the treatment of PTCL, but may have some activity against B-cell lymphomas as well ( Tula-Sanchez et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HDACIs are a class of small-molecules that inhibit the activity of Zn 2+ -dependent classical HDACs (class I, II, and class IV HDACs) and promote acetylation of histone and nonhistone protein substrates. Originally, HDACIs were known for their varied cellular effects on cancer cells, such as inhibiting cell proliferation and stimulating differentiation or apoptosis, advocating their usefulness in anticancer drug discovery, and development [80,81]. Now, it is recognized HDACIs induce an array of cellular effects [69,82,83].…”
Section: Histone Deacetylase Inhibitors (Hdacis)mentioning
confidence: 99%